ON DEFERRED CESARO MEAN IN PARANORMED SPACES - Ercan, Sinan (Kangwon-Kyungki Mathematical Soc, 2021)
The aim of the present study is to introduce the concepts of deferred statistical convergence, deferred statistical Cauchy sequence and deferred Cesaro summability in paranormed spaces. We investigate some properties of these concepts and some inclusion relations with examples.
Keywords: statistical convergence; deferred statistical convergence; paranormed space